Delay on pulmonary tuberculosis diagnosis in low-incidence countries : a systematic review - Afonso, Nuno Gonçalo do Amparo Leitão (2025)
ABSTRACT - Background: Reducing tuberculosis (TB) mortality and morbidity requires minimal delay from onset of symptoms to diagnosis (total delay), and its two subcomponents (patient and healthcare delays). This systematic review aims to study pulmonary TB diagnosis delay associated factors in low-incidence countries. Methods: Articles assessing TB delay associated factors from 2009 to 2019 in lowincidence countries (<20 cases/100,000 inhabitants) were included. Web of Science, Scopus, Medline and The Cochrane Library were searched. Double screening was performed, followed by single article extraction with validation. Risk of bias was assessed using Joanna Briggs Institute Tools. Meta-analysis was planned whenever 5 studies were available, otherwise a qualitative synthesis would be conducted. Each outcome’s quality of evidence was evaluated using GRADE methodology. Results: From 2,623 articles extracted, 18 articles met the selection criteria. Due to lack of data, no meta-analysis was performed. Qualitative synthesis showed that longer total and patient delays were found among foreigners, while access to diagnostic technology was associated with shorter healthcare delay. Discussion: Longer delays than recommended were found, and country of origin is an important factor for it. Very low overall quality of evidence was found for all outcomes. Further studies are required to assess the robustness of these findings.